Tools Evaluating Child Oral Health-Related Quality of Life - Hollis Haotian Chai; Sherry Shiqian Gao; Kitty Jieyi Chen; Edward Chin Man Lo; Duangporn Duangthip; Chun Hung Chu (Elsevier, 2024)
Objectives: This study aimed to systemically review the tools developed for evaluating oral health-related quality of life (OHRQoL) in preschool children. Methods: Two reviewers systematically searched English-language publications within PubMed, Embase, Scopus, and Web of Science. They screened the titles and abstracts and retrieved the full texts of the selected publications. Studies which developed, validated, or culturally adapted an OHRQoL tool used in preschool children were included. They recorded information regarding tool characteristics, item configuration, discriminative validation, the aim of assessment, and the target group. Results: The study included 59 publications and identified 12 tools for assessing OHRQoL in preschool children. Seven tools were tailored for preschool ages. Most of the scales were generic oral health measures. Dental caries was the most commonly used oral condition for assessing a tool's discriminative validity. Eight tools required parental proxy reports. Three tools were both child-administrated and parent-administrated. One tool was designed to be answered solely by children. Ten tools assessed the oral health-related impact on children, including oral condition-related, functioning, environmental, and emotional/social domains. Four tools included items regarding the impact on both children and family. Conclusions: This review identified 12 tools developed for evaluating OHRQoL in preschool children, 7 of which were tailored for preschool age. The 12 tools were validated but incomprehensive due to the subjective and multidimensional nature of the OHRQoL concept. Researchers can choose a suitable tool for their studies by understanding the basic characteristics and item setting of the tools. Researchers can have an overview of the tools developed for evaluating OHRQoL in preschool children. They can use the findings from this review to choose a suitable tool for their studies regarding the OHRQoL in preschool children.